Clinical and Endoscopic Recurrence after Surgical Resection in Patients with Crohn's Disease - Yang Woon Lee; Kang-Moon Lee; Woo Chul Chung; Chang Nyol Paik; Hea Jung Sung; You Suk Oh (Intestinal Research, 2014)
Background/AimsThe natural history of Crohn's disease (CD) is characterized by a remitting and relapsing course and a considerable number of patients ultimately require bowel resection. Moreover, postoperative recurrence is very common. Relatively few studies have investigated the postoperative recurrence of CD in Korea. The aim of the current study was to assess postoperative recurrence rates - both clinical and endoscopic - in CD as well as factors influencing postoperative recurrence.MethodsElectronic medical records of patients who underwent surgery due to CD were reviewed and analyzed. Patients with incomplete surgical resection, a follow-up period of less than a year, and a history of strictureplasty or perianal surgery were excluded.ResultsOf 112 CD patients, 39 patients had history of bowel resection, and 34 patients met the inclusion criteria. Among them, 26 were male (76%) and the mean age of onset was 32.8 years. The mean follow-up period after operation was 65.4 months. Cumulative clinical recurrence rates were 8.8%, 12.5%, and 33.5% at 12, 24, and 48 months, respectively. Use of immunomodulators for prophylaxis was the only predictor of clinical recurrence in univariate analysis (P=0.042). Of 21 patients who had undergone follow-up colonoscopy after surgery, cumulative endoscopic recurrence rates were 33.3%, 42.9%, and 66.1% at 6, 12, and 24 months, respectively. No significant predicting factor for endoscopic recurrence was detected.ConclusionsPostoperative recurrence rates in Korean patients with CD are high, and endoscopic recurrence rates are comparable to those reported from Western studies. Appropriate medical prophylaxis seems to be important for preventing postoperative recurrence in CD.